Pathways for reduction of HIV‐related stigma: a model derived from longitudinal qualitative research in Kenya and Uganda. Issue 12 (7th December 2020) - Camlin, Carol S; Charlebois, Edwin D; Getahun, Monica; Akatukwasa, Cecilia; Atwine, Frederick; Itiakorit, Harriet; Bakanoma, Robert; Maeri, Irene; Owino, Lawrence; Onyango, Anjeline; Chamie, Gabriel; Clark, Tamara D; et al.
Abstract: Introduction: The rollout of antiretroviral therapy (ART) has been associated with reductions in HIV‐related stigma, but pathways through which this reduction occurs are poorly understood. In the newer context of universal test and treat (UTT) interventions, where rapid diffusion of ART uptake takes place, there is an opportunity to understand the processes through which HIV‐related stigma can decline, and how UTT strategies may precipitate more rapid and widespread changes in stigma. This qualitative study sought to evaluate how a UTT intervention influenced changes in beliefs, attitudes and behaviours related to HIV. Methods: Longitudinal qualitative in‐depth semi‐structured interview data were collected within a community‐cluster randomized UTT trial, the Sustainable East Africa Research in Community Health (SEARCH) study, annually over three rounds (2014 to 2016) from two cohorts of adults (n = 32 community leaders, and n = 112 community members) in eight rural communities in Uganda and Kenya. Data were inductively analysed to develop new theory for understanding the pathways of stigma decline. Results: We present an emergent theoretical model of pathways through which HIV‐related stigma may decline: internalized stigma may be reduced by two processes accelerated through the uptake and successful usage of ART: first, a reduced fear of dying and increased optimism for prolonged and healthy years of life; second, a restoration of perceived social value and fulfilment of subjective role expectations via restored physical strength and productivity. Anticipated stigma may be reduced in response to widespread engagement in HIV testing, leading to an increasing number of HIV status disclosures in a community, "normalizing" disclosure and reducing fears. Improvements in the perceived quality of HIV care lead to people living with HIV (PLHIV) seeking care in nearby facilities, seeing other known community members living with HIV, reducing isolation and facilitating opportunities for social support and "solidarity." Finally, enacted stigma may be reduced in response to the community viewing the healthy bodies of PLHIV successfully engaged in treatment, which lessens the fears that trigger enacted stigma; it becomes no longer socially normative to stigmatize PLHIV. This process may be reinforced through public health messaging and anti‐discrimination laws. Conclusions: Declines in HIV‐related stigma appear to underway and explained by social processes accelerated by UTT efforts. Widespread implementation of UTT shows promise for reducing multiple dimensions of stigma, which is critical for improving health outcomes among PLHIV.